Evaluation of Education Development Centers for Medical Sciences: Challenges and Strategies - Ali Akbar Haghdoost; Ali Akbar Haghdoost; Mozhgan Emami; Reza Dehnavieh; Nader Momtazmanesh; Farangis Shoghi Shafagh Aria; Mohammad Hossien Mehrolhassani (Strides in Development of Medical Education, 2015)
Background & Objective: The main objective of medical education is the training of competent and qualified personnel to maintain and improve public health In this regard education development centers (EDC) for medical sciences have been established to provide and assess the quality of education Therefore due to the need for these centers this study aimed to examine their challenges and provide strategies to improve their performance Methods: An applied and qualitative study was carried out in 2013 The study population was 288 members of the managers and personnel of study centers and development offices of faculties educational deputies heads of universities and faculty members Data was collected during a 2day scheduled conference in the form of 5 key lectures 3 panels and 6 Focus Group Discussions Data analysis was performed using framework analysis Results: In the correct establishment of the centers 7 key challenges and 18 subchallenges were identified Within the framework of the educational governance and leadership components such as policy making monitoring evaluation and predisposing components of implementation like structure manpower and processes were identified The relationship between policy making evaluation and subcomponents is defined by two key factors of knowledge management and communications Conclusion: EDC centers have been challenged because of moving away from the original position of knowledge management and communications in the field of governance to ensure and improve the quality of education The 3 trends of integration of education and service delivery privatization of services and lack of clarity of interactions between public and private sector have exacerbated these challenges